Chemosensor Strip from Kepok Banana Bracts Extract (Musa paradisiaca L.) for Detection of Tuna Freshness - Joana Sugiarto; Zayyani Trianti Fatmasari; Sugiyani Puji Lestari; Bambang Purwono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Anthocyanins as chemosensory compounds for amines have been tested in this study. Because anthocyanins are sensitive to pH changes, while amines have an alkaline nature, they can cause structural changes in anthocyanins, resulting in changes in the color of anthocyanins. The source of anthocyanins was the Kepok banana bracts (Musa paradisiaca L.), which were extracted using a mixture of ethanol:HCl 0.15% (3:2). The types of anthocyanin compounds were characterized using a UV-Vis spectrophotometer. The anthocyanin content obtained varied from 1.26 mg/100 g to 5.08 mg/100 g. The type of anthocyanin in the Kepok banana bracts was found as a cyanidin-3-rutinoside with maximum absorption at 513 nm at pH 1. The color of anthocyanin extract varied with changes in pH; it turned red in acid and faded in neutral solutions. The green color in the alkaline solution changes to brownish-yellow was associated with anthocyanin degradation. The color change at different pH indicates that banana bracts are regarded as a potential chemosensory compound to detect tuna freshness. The chemosensor was applied to a cellulose-based strip and exhibited a color change that corresponded to the increase in pH and was comparable to the results of the pH meter measurement. The structural changes of anthocyanin before and after the tuna freshness test were identified by the FTIR-ATR, indicating a change in the anthocyanin structure. Tuna freshness began to diminish after being stored for 12 and 24 hours at room temperature, marked by a color change of the paper strip to colorless and blackish gray.